Research on China’s renewable portfolio standards from the perspective of policy networks - Li, Yun; Zhang, Feng; Yuan, Jiahang (Journal of cleaner production, 2019)
Currently, wind and solar energy have not been well utilized in China, and the rate of abandoned wind and solar facilities in China is increasing annually. Renewable portfolio standards (RPS) are an effective system for promoting large-scale renewable energy integration and consumption and realizing the goal of renewable energy development. To clarify the interactive relationship between the different levels and multiple actors in RPS, this paper uses policy network theory to analyze the interactive relationship of stakeholders from the three aspects of network subject, network structure and network interaction. The policy network of the RPS consists of the policy community, professional network, intergovernmental network, producer network and issue network. Under the RPS, to meet their own needs, participants affect the formulation and implementation of the RPS through the actions of confrontation, alliance, competition and cooperation. In different stages of developing the RPS, the openness and integration of policy networks change accordingly. This study overcomes the limitations of past simple analyses of the actor relationship in the policy process and thereby offers certain reference significance. •The actors of RPS policy networks are analyzed.•This paper analyze the game relationship of the stakeholders from three aspects.•This research reveals the network relationship between multiple stakeholders.•This study breaks through the limitations of past analysis of actor relationship.